Wellbeing and Fair Thrill-Seeking Rewards - Kantarelis, Demetri (Advances in Social Sciences Research Journal, 2024)
A theory for wellbeing is proposed, developed on the assumption that consumers, deciding based on various risk-preference attitudes, consider fair thrill-seeking activities for inclusion in a portfolio of goods and services. Fair are those activities governed by rules or regulations, those that enable consumers to safely get an adrenaline shot; for example, skydiving, is considered fair (safe) when it follows rules and regulations and unfair (unsafe) if undertaken subject to non-compliance with, or lack of, rules and regulations. More specifically, it is assumed that consumer wellbeing depends on a fair diversified portfolio of risk-preference expected reward outcomes and their variabilities. In turn, by relying on a simulation-based thought experiment, it is shown that consumers may choose to place more or less importance (expenditures) on various fair rewards to end up with optimum solutions that resemble conventional modern portfolio theory results.